Safety nets and benefit dependence - Carcillo, Stéphane (Emerald, 2014)
Patterns of transitions into and out of benefit receipt are important measures of the effectiveness of social protection system, which play a important role in response to economic downturns. This volume contains new research on the dynamics of social insurance, including articles that provide evidence on benefit dependence from various countries.
Keywords: Labor economics.; elektronické knihy; electronic books